2023
DOI: 10.1002/advs.202206955
|View full text |Cite
|
Sign up to set email alerts
|

HOOK1 Inhibits the Progression of Renal Cell Carcinoma via TGF‐β and TNFSF13B/VEGF‐A Axis

Abstract: Accumulating evidence shows HOOK1 disordered in human malignancies. However, the clinicopathological and biological significance of HOOK1 in renal cell carcinoma (RCC) remains rarely studied. In this study, the authors demonstrate that HOOK1 is downregulated in RCC samples with predicted poorer clinical prognosis. Mechanistically, HOOK1 inhibits tumor growth and metastasis via canonical TGF-𝜷/ALK5/p-Smad3 and non-canonical TGF-𝜷/MEK/ERK/c-Myc pathway. At the same time, HOOK1 inhibits RCC angiogenesis and sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Meanwhile, an elevated activation of TGF-β pathway was also observed, corroborating prior evidence for a beneficial role of TGF-β in ccRCC (Fig. 4 A) [ 38 ]. In our previous findings, we have identified and validated dichotomous ccRCC immune subtypes with prognosis and TKI responses [ 39 ].…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, an elevated activation of TGF-β pathway was also observed, corroborating prior evidence for a beneficial role of TGF-β in ccRCC (Fig. 4 A) [ 38 ]. In our previous findings, we have identified and validated dichotomous ccRCC immune subtypes with prognosis and TKI responses [ 39 ].…”
Section: Resultssupporting
confidence: 87%
“…Abnormally high levels of VEGF-A primarily control angiogenesis, which is the development of new blood vessels from already existing ones. This spike in VEGF-A is frequently triggered by tumor hypoxia during lesion expansion, but it can also arise from defects in the primary HIF pathway ( 22 ). Additionally, disruptions that occur during other stages of vascular development, i.e., PDGF-BB and Notch, contribute to and hasten the vascularization of tumors ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer cells, it was observed that while SHP2 positively regulates TEM, HOOK1 has the opposite effect [ 24 ]. Nonetheless, other studies have linked HOOK1 to the progression of different types of tumors independently to its proposed interaction with SHP2 [ 20 , 25 , 26 ]. Hence, the precise role of HOOK1 in cancer and its underlying mechanism remain unclear.…”
Section: Introductionmentioning
confidence: 99%